Brazil climate highlights 2023 - Pampuch, Luana Albertani [UNESP]; Bueno, Paola Gimenes; Reboita, Michelle Simões; Tomaziello, Ana Carolina Nóbile; Nunes, Ana Maria Pereira; Cardoso, Andressa Andrade; Coelho, Caio A. S.; Carpenedo, Camila Bertoletti; Vasconcelos, Francisco das Chagas; Gomes, Helber Barros; Pinheiro, Henri Rossi; Braga, Hugo Alves; et al. (Wiley, 2025)
In the year 2023, the Earth experienced the highest near-surface temperature anomalies ever recorded until then. In addition, several extreme weather and climate events occurred around the world, including in Brazil. In this context, the primary objective of this study is to analyze the anomalous temperature and precipitation patterns observed in Brazil during 2023, along with the most significant extreme events. Different datasets and methodologies were applied. The north coast of the state of São Paulo had the highest accumulation of rainfall recorded in Brazil in a single day. September, October, and November 2023 experienced the large precipitation deficits over the Amazon region, leading to a very intense and prolonged drought. The south of Brazil was affected by a large amount of precipitation in a short time, associated with cyclones, resulting in fatalities and economic losses. Southeast and Central-West Brazil experienced two intense heatwaves in the austral spring, breaking daily temperature records in major cities like São Paulo and Rio de Janeiro. Overall, this study describes the main physical processes responsible for these extremes, along with the socioenvironmental impacts caused by most of them.